Best Answer

Add 14 to both sides.

3x = 2x + 23

Subtract 2x from both sides.

x = 23

Check it.

3 x 23 - 14 = 55

2 x 23 + 9 = 55

It checks.

Q: What is x in 3x minus 14 is equal to 2x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-2x -11y - 13

(x - 2)(2x + 7)

The given expression can be simplified to: 10x -5

X=27

x = 15

Related questions

-2x -11y - 13

It can't be solved because the discriminant of this quadratic equation is less than zero

(x - 2)(2x + 7)

5m + 7 - 2m - 1 = 3m + 6

The given expression can be simplified to: 10x -5

2x minus 3x is equal to -x.

X=27

2(x - 7)(x - 1)

2x - 12 > 2 + x x - 12 > 2 x > 14

This expression factors as x -1 quantity squared.

x = 15

2x2 + 2x - 8 = 2(x2 + x - 4). This can take any value greater than or equal to -8.5